1989
DOI: 10.1136/gut.30.8.1132
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of endoscopic endoprosthesis versus operative bypass in malignant obstructive jaundice.

Abstract: In recent years, endoscopically placed endoprosthesis has become an alternative to traditional operative biliary-digestive bypass in palliative treatment of patients with non-resectable biliary obstruction caused by malignant stricture of the extrahepatic bile duct. In an uncontrolled series the endoscopic approach has been recommended as the treatment of choice.' Alternatively surgery has been recommended primarily because 13% of the survivors needed a later operation for duodenal obstruction.2 The combined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
224
1
14

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(241 citation statements)
references
References 4 publications
2
224
1
14
Order By: Relevance
“…However, recurrence of jaundice with or without cholangitis is more frequently reported after the use of stents. Four prospective randomized trials have shown that recurrent jaundice/cholangitis was more frequent after stenting (up to 38%) than after bypass surgery (3-10%) [23][24][25][26]. Whether these short periods of recurrent jaundice/cholangitis and subsequent stent changes have any effects on the quality of life of these patients remains to be analyzed.…”
Section: Jaundicementioning
confidence: 99%
“…However, recurrence of jaundice with or without cholangitis is more frequently reported after the use of stents. Four prospective randomized trials have shown that recurrent jaundice/cholangitis was more frequent after stenting (up to 38%) than after bypass surgery (3-10%) [23][24][25][26]. Whether these short periods of recurrent jaundice/cholangitis and subsequent stent changes have any effects on the quality of life of these patients remains to be analyzed.…”
Section: Jaundicementioning
confidence: 99%
“…[16,18]. While overall survival did not differ between treatments, they demonstrated that endoscopic stenting had a lower rate of short-term complication than surgical treatment.…”
Section: Surgerymentioning
confidence: 98%
“…Although very effective in relieving obstruction and preventing reocclusion due to direct tumor invasion, surgical biliary bypass (e.g. hepatojejunostomy) is associated with a high rate of complications, a long hospital stay and consequently high costs [16][17][18][19]. Percutaneous insertion of plastic and metallic stents is also effective in the palliation of malignant obstruction, especially in the presence of dilated intra-hepatic radicals.…”
Section: Treatmentmentioning
confidence: 99%
“…[47][48][49][50] Although nonoperative palliation is associated with decreased procedure-related morbidity and mortality and a shorter initial hospitalization, its principle limitation is the tendency of the stent to occlude from biliary sludge and debris. Stent occlusion may occur in 35 percent of patients, and rehospitalization for treatment of cholangitis secondary to stent occlusion impacts on the quality of life and may outweigh the morbidity of operative palliation.…”
Section: Operative Versus Nonoperative Palliationmentioning
confidence: 99%